PL03.4.A Factors associated with health-related quality of life (HRQoL) deterioration in glioma patients during the progression-free survival period. (9th September 2021) - Coomans, M; Dirven, L; Aaronson, N; Baumert, B; van den Bent, M; Bottomley, A; Brandes, A; Chinot, O; Coens, C; Gorlia, T; Herrlinger, U; Keime-Guibert, F; et al.
Abstract: BACKGROUND: Maintenance of functioning and wellbeing during the progression-free survival (PFS) period is important for glioma patients. This study aimed to determine whether health-related quality of life (HRQoL) can be maintained during progression-free time, and factors associated with HRQoL deterioration in this period. MATERIAL AND METHODS: We included longitudinal HRQoL data from previously published clinical trials in glioma. The percentage of patients with stable HRQoL until progression was determined per scale and at the individual patient level (i.e. considering all scales simultaneously). We assessed time to a clinically relevant deterioration in HRQoL, expressed in deterioration-free survival and time-to-deterioration (the first including progression as an event). We also determined the association between sociodemographic and clinical factors and HRQoL deterioration in the progression-free period. RESULTS: 5539 patients with at least baseline HRQoL scores had a median time from randomization to progression of 7.6 months. Between 9%-29% of the patients deteriorated before disease progression on the evaluated HRQoL scales. When considering all scales simultaneously, 47% of patients deteriorated on ≥1 scale. Median deterioration-free survival period ranged between 3.8–5.4 months, and median time-to-deterioration between 8.2–11.9 months. For most scales, only poor performance status was independently associated with clinically relevant HRQoL deterioration in the progression-free period. CONCLUSION: HRQoL was maintained in only 53% of patients in their progression-free period, and treatment was not independently associated with this deterioration in HRQoL. Routine monitoring of the patients' functioning and well-being during the entire disease course is therefore important, so that interventions can be initiated when problems are signalled.